HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA LANSIA PENDERITA HIPERTENSI - Devi Widyaningrum; Dwi Retnaningsih; Tamrin Tamrin (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2019)
Background: Family support a trait that supportive and always provides help and assistance if needed by one of the family members. Form of family support in the form of information, assessment, instrumental, and emotional. According to records from the Health Profile of Central Java in 2017, the number of patients with hypertension was 8355 people. Family support also affects the occurrence of medication adherence in patients with hypertension. The purpose of this study was to determine the relationship of family support with medication adherence in elderly people with hypertension in the Gayamsari Community Health Center in Semarang.Research Methodology: This study uses quantitative research with a descriptive correlation method with a cross sectional approach and research instruments using questionnaires. The sample technique used Purposive Sampling Technique. The population 210 elderly and the sample 137 elderly. Analysis of the data used is the Spearman Rank test.Results: The results of this study were obtained from 62 elderly respondents with good family support, 46 (33,6%) had high medication adherence and 15 elderly received less family support, 15 (10,9%) had moderate medication adherence . Spearman Rho statistical test results showed that ρ value 0,000 ≤α 0,05. Correlation coefficient 0,874 which means there is a relationship of family support with medication adherence in elderly people with hypertension in the Gayamsari Community Health Center in Semarang city very strong.Conclusion: There is a relationship of family support with medication adherence in elderly patients with hypertension in the Gayamsari Community Health Center in Semarang.